The effects of elastic band exercises and nutritional education on frailty, strength, and nutritional intake in elderly women - Bong, Yena; Song, Wook (Journal of exercise nutrition & biochemistry, 2020)
The purpose of this study was to examine the effects of elastic band exercises and nutritional education, as well as to identify the factors influencing frailty, strength, and nutritional intake of elderly women. The subjects in this study were 30 elderly women who were divided into four groups. All groups agreed to participate in four programs: health education only (HE), elastic band exercises only (EX), nutritional education only (NU), and elastic band exercises plus nutritional education (EX+NU). Frailty was evaluated by measuring the frailty factors according to Fried et al. Leg strength was measured using a leg-extension machine. Nutritional intake was assessed by the 24-hour recall method and food records. Nutritional intake was analyzed by CAN Pro 5.0 program. After three months, the prevalence of frailty significantly decreased in the EX+NU group (P=0.013) compared with that of the HE group (P=0.088). There was significant improvement in leg strength in both the EX (P=0.012) and EX+NU groups (P=0.003) compared with that of the HE group (EX, P=0.005; EX+NU, P=0.002). The nutritional intake significantly decreased in the EX group compared with that of the HE group (P<0.05, P<0.05). The combination of elastic exercises and nutrition education had positive effects on frailty and leg strength, while having negative effects on total calories, carbohydrate, sodium, and iron intake in elderly women. Elastic exercises only had positive effects on leg strength while having negative effects on nutritional intake in elderly women.